Hypomineralized molars and incisors of unknown origin: treatment outcome at age 18 years - I. MEJÀRE, E. BERGMAN, & M. GRINDEFJORD (Paediatric Dentistry, 2005)
To assess the outcome of treatment of hypomineralized molars and incisors of unknown aetiology (MIH) in 18-year-olds.